2020
DOI: 10.1177/0954405420960920
|View full text |Cite
|
Sign up to set email alerts
|

Towards intelligent CFRP composite machining: Surface analysis methods and statistical data analysis of machined fibre laminate surfaces

Abstract: Many carbon fibre reinforced polymer composite parts need to be edged trimmed before use to ensure both geometry and mechanical performance of the part edge matches the design intent. Measurement and control of machining induced surface damage of composite material is key to ensuring the part retains its strength and fatigue properties. Typically, the overall surface roughness of the machined face is taken to be an indicator of the amount of damage to the surface, and it is important that the measurement and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…These results are linked with the high fracture toughness of the rubber modified epoxy, limiting the crack growth along the matrix in 135° fibre orientation, thus decreasing the amount of pull-out material and subsurface damage. As shown in Figure 10 and previously in the literature [12], [13], [40], fibre orientation has a strong influence on the generated surface topography after machining. DGEBA samples represent the reference material in Figure 11.…”
Section: Subsurface Damage Analysis In Relation To Chip Formation Mec...supporting
confidence: 76%
See 1 more Smart Citation
“…These results are linked with the high fracture toughness of the rubber modified epoxy, limiting the crack growth along the matrix in 135° fibre orientation, thus decreasing the amount of pull-out material and subsurface damage. As shown in Figure 10 and previously in the literature [12], [13], [40], fibre orientation has a strong influence on the generated surface topography after machining. DGEBA samples represent the reference material in Figure 11.…”
Section: Subsurface Damage Analysis In Relation To Chip Formation Mec...supporting
confidence: 76%
“…The volume of indentations (craters) observed on the 135° plies was calculated using the Dragonfly CT segmentation software (Figure 7b)). These have previously reported during machining of CFRPs [12], [13] and it was found that they adversely affected the mechanical properties of the samples namely flexural and compressive strength [14], [41], [42]. All the machined surfaces showed significant matrix smearing across all fibre orientations.…”
Section: Subsurface Damage Analysis In Relation To Chip Formation Mec...mentioning
confidence: 56%
“…4 In the current dynamic era with big challenges, disruptions and uncertainties, new requirements and technologies are emerging at an unprecedented speed. 5,6 In engineering area, new manufacturing equipment and technologies, measurement methods and technologies as well as related upstream technologies are emerging day by day, [7][8][9] only the researchers with innovation capability can keep up with the development pace of new technologies. The lack of originality will lead to weak competitiveness for a person, a company as well as for a country.…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of the cracks plays a fundamental role in the appearance of defects in the mechanical surface, such as surface roughness or sub-surface damage. A clear increase in these variables is observed in fibre orientations greater than 90 • due to the fact that the great bending effect causes the fibre breakage to occur in a very irregular way below the cutting surface as well as a significant increase in the fibre matrix debonding extension into the sub-surface damage [40,41].…”
Section: Introductionmentioning
confidence: 99%